Analysis of Demand for Material Variations Effect on Material Procurement Process Time at PT XYZ Using the Structural Equation Modeling Method: Analisis Pengaruh Variasi Permintaan Material Terhadap Waktu Proses Pengadaan Material Di PT XYZ Menggunakan Metode Structural Equation Modeling - Difa Nur Pratiwi; Mega CPA. Islami (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Effective material procurement is an important factor for the success of a company's operations, especially in a manufacturing industry with a high level of complexity such as that operated by PT XYZ. In this case, effective material management not only affects the smoothness of the production process, but also contributes to the company's overall competitiveness and performance. A study on the influence of material variations listed in the request letter and the time required for material procurement at PT XYZ was conducted to reduce risks that could potentially disrupt material management performance. This study is based on statistical analysis. The results of the hypothesis test show that the relationship between VJ (Type Variation) and WP (Procurement Time) is significant, with a t-statistic of 2.318 and a p-value of 0.020 <0.05. The relationship between VS (Specification Variation) and WP also shows significant results with a t-statistic of 2.411 and a p-value of 0.016. Thus, VJ and VS have a significant effect on WP. By understanding this correlation, companies are expected to be able to identify areas that need improvement in the procurement process, as well as reduce the risk of delays that can affect overall performance.